The treatment of female characters in Thomas Hardy's far from the madding crowd, the return of the native, the mayor of casterbridge and tess of the d'urbervilles - Akhter, Bilkis (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
The aim of the thesis is to analyse the presentation of women characters in Thomas Hardy's selected novels and to explore to what extent Hardy accepts the Victorian view of women. Is Hardy's approach to women often influenced by Victorian society in which he lives? Does he show sympathy or does he put much blame on women while presenting them in his novels? At that time, the society itself was largely controlled by men and male superiority was not questioned at all. As a result, women suffered injustices at the hands of the men. Women are mothers, wives and lovers. They are exposed to different roles during different stages of their lives. In the course of time while performing their legitimate duties they are sometimes oppressed by men rather than they oppress men. They are more victims than victimizers. They are not prone to sinning, rather they are sinned against. Thomas Hardy in his novels shows women performing their different roles in various manners. Sometimes they are independent and sometimes they have to depend on others for their survival. They frequently become the victims of male domination or patriarchy. The study will also explore the issues of women's oppression in the Victorian society on the basis of the selected novels. In general, female characters in Hardy's novels are always depicted as docile and submissive. Hardy's major female characters, despite their individuality, share the same sentiments and suffer from the same class and gender oppression. It is always their effort to fight back that bring them anguish and tragedy. Some of them though hardened and stoic are still unable to overcome their social and economic deprivations. In Hardy's celebrated novels, Far from the Madding Crowd (1874), The Return of the Native (1878), The Mayor of Casterbridge (1886) and Tess of the d'Urbervilles (1891) women are subjected to all kinds of human indignities by men. They always fail in their attempts to extricate themselves from their social and economic entrapment. Hardy's enigmatic and unforgettable heroines, Bathsheba Everdene, Fanny Robin, Eustacia Vye, Thomasin Yeobright, Susan Henchard, Elizabeth-Jane, Lucetta Templeman and Tess Durbeyfield in their actions, reactions and interactions are embodiments of social wretchedness and inferiority. This thesis analyses the treatment of women in the selected novels in an attempt to explore feminist ideas in his works. The study also explores Hardy's novels from the Islamic perspective on women.